A descriptive analysis of anglicisms used in ecuadorian magazines - Hidalgo Durán, Saskia Pamela (2011)
The theme of this research done in order to achieve the Bachelor´s Degree in Teaching English as a Foreign Language is a descriptive analysis of anglicisms used in Ecuadorian magazines. Its general objective is to research on the linguistic phenomenon of anglicisms used in Ecuadorian magazines. This research has been developed in Quito, Ecuador. The sample of the investigation has been chosen from six national magazines published in Ecuador, which have been divided into 3 groups of two magazines each group. The categories of magazines mentioned before were, cultural magazines, scholarly magazines and general interest magazines. The research´s population got a number of 336 anglicisms collected from the six magazines, which have been the main source, where data was collected. The sample has been defined by the selection of 30 anglicisms, the most used and representative of the population in order to analyze them. The method used in order to analyze the anglicisms was the qualitative and quantitative scientific method of analysis and collection of information.